Legal Analysis of Consumer Protection: Certainty Regarding Objections to Consumer Dispute Settlement Agency Arbitration Award - David Prawira; R.M. Gatot P. Soemartono (Journal of Law, Politic and Humanities, 2025)
Consumer protection laws serve as a vital safeguard for citizens engaged in transactions involving products and services. The Consumer Dispute Settlement Agency plays an essential role in addressing consumer issues through arbitration, conciliation, or mediation. Among these methods, arbitration is particularly effective due to its final and binding nature. However, a significant limitation arises while Consumer Dispute Settlement Agency's arbitration decisions are deemed final and binding within the agency, they are subject to appeal in district courts, leading to complications in enforcement and legal uncertainty. This research aims to explore the implementation of consumer protection laws and the legal certainty surrounding the resolution of consumer disputes through Consumer Dispute Settlement Agency. Employing a normative research methodology, this study examines the challenges posed by appeals against Consumer Dispute Settlement Agency's arbitration decisions, particularly when the legal framework supporting these decisions becomes outdated or inadequate. To enhance legal certainty in consumer dispute resolution, a revision of the consumer protection law is necessary. Such revisions could streamline the arbitration process and reinforce the binding nature of Consumer Dispute Settlement Agency's decisions, ultimately strengthening consumer rights and ensuring more effective dispute resolution